A systematic review of droplet and aerosol generation in dentistry. (February 2021) - Innes, N.; Johnson, I.G.; Al-Yaseen, W.; Harris, R.; Jones, R.; KC, S.; McGregor, S.; Robertson, M.; Wade, W.G.; Gallagher, J.E.
Abstract: Objectives: This review aimed to identify which dental procedures generate droplets and aerosols with subsequent contamination, and for these, characterise their pattern, spread and settle. Data resources: Medline(OVID), Embase(OVID), Cochrane Central Register of Controlled Trials, Scopus, Web of Science and LILACS databases were searched for eligible studies from each database's inception to May 2020 (search updated 11/08/20). Studies investigating clinical dental activities that generate aerosol using duplicate independent screening. Data extraction by one reviewer and verified by another. Risk of bias assessed through contamination measurement tool sensitivity assessment. Study selection: A total eighty-three studies met the inclusion criteria and covered: ultrasonic scaling (USS, n = 44), highspeed air-rotor (HSAR, n = 31); oral surgery (n = 11), slow-speed handpiece (n = 4); air-water (triple) syringe (n = 4), air-polishing (n = 4), prophylaxis (n = 2) and hand-scaling (n = 2). Although no studies investigated respiratory viruses, those on bacteria, blood-splatter and aerosol showed activities using powered devices produced greatest contamination. Contamination was found for all activities, and at the furthest points studied. The operator's torso, operator's arm and patient's body were especially affected. Heterogeneity precluded inter-study comparisons but intra-study comparisons allowed construction of a proposed hierarchy of procedure contamination risk: higher (USS, HSAR, air-water syringe, air polishing, extractions using motorised handpieces); moderate (slow-speed handpieces, prophylaxis, extractions) and lower (air-water syringe [water only] and hand scaling). Conclusion: Gaps in evidence, low sensitivity of measures and variable quality limit conclusions around contamination for procedures. A hierarchy of contamination from procedures is proposed for challenge/verification by future research which should consider standardised methodologies to facilitate research synthesis. Clinical significance: This manuscript addresses uncertainty around aerosol generating procedures (AGPs) in dentistry. Findings indicate a continuum of procedure-related aerosol generation rather than the common binary AGP or non-AGP perspective. The findings inform discussion around AGPs and direct future research to support knowledge and decision making around COVID-19 and dental procedures.